Impact of local finance and popular participation on local development. Comparative study between the Syrian Arab Republic and the Arab Republic of Egypt - Shaar, Asem Waled; Arab, Walid Akel (Journal of Economic, Administrative and Legal Sciences, 2022)
Local finance and popular participation have a critical impact on local development, To illustrate this, the researcher studied this paper through two requests. In the first request, the researcher explained what local financing was and its conditions and the problems of local financing. The researcher explained some examples of the role of local finance and popular participation in local development in both the Syrian Arab Republic and the Arab Republic of Egypt through the second requirement. The researcher relied on the comparative analytical descriptive approach. The researcher has used several means to gather his information, including legal sources, scientific references, some academic studies and some practical examples applied within the local administration units.